2014
DOI: 10.1177/0333102414535113
|View full text |Cite
|
Sign up to set email alerts
|

Vestibular migraine

Abstract: As randomized controlled treatment trials are still missing in vestibular migraine, the therapeutic recommendations for vestibular migraine are currently based on the guidelines of migraine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
91
2
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 94 publications
(99 citation statements)
references
References 64 publications
3
91
2
3
Order By: Relevance
“…Cortical spreading depression (CSD) in both multisensory vestibular areas of the cortex and brainstem was used as an explanation for ' aura'-like dizziness/vertigo attacks with consecutive headache. However, an isolated CSD, which is limited to the brain stem without causing any other symptoms, is not very likely 25 . Some authors suggested a genetic inheritance.…”
Section: Pathophysiologymentioning
confidence: 99%
See 2 more Smart Citations
“…Cortical spreading depression (CSD) in both multisensory vestibular areas of the cortex and brainstem was used as an explanation for ' aura'-like dizziness/vertigo attacks with consecutive headache. However, an isolated CSD, which is limited to the brain stem without causing any other symptoms, is not very likely 25 . Some authors suggested a genetic inheritance.…”
Section: Pathophysiologymentioning
confidence: 99%
“…The duration of attacks can vary from a few seconds (10% of patients) to some minutes (30% of patients), some hours (30% of patients) and even up to a few days (30% of patients) 25 . Only 10-30% of patients described a typical vestibular aura.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…There must be at least five episodes with vestibular symptoms of moderate or severe intensity lasting between five minutes and 72 hours, a current or past history of migraine without aura or migraine with aura, and at least 50% of the episodes have to be associated with migrainous features such as characteristic migraine headache, photophobia, phonophobia or visual aura. [4] Less than 10% of patients with VM meet these criteria. [3][4][5][6][7] Because there is no specific symptom to diagnose VM, its diagnosis is based on patient history.…”
mentioning
confidence: 99%
“…[4] Less than 10% of patients with VM meet these criteria. [3][4][5][6][7] Because there is no specific symptom to diagnose VM, its diagnosis is based on patient history. According to the classification by IHS and Neuhauser, phonophobia and photophobia during headache are both probable and definite diagnostic criteria.…”
mentioning
confidence: 99%